PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 5 KOTO XI TARUSAN - Roza, Yulia; Rismen, Sefna; Pratiwi, Merina (STKIP PGRI Sumbar, 2013)
The background of this research by students learning motivation and comprehension of mathematical concept was low. It could be seen from studentsâdemotivated in learning mathematic and also most of them did not do their exercises. One way to solve this problem was by implementing active learning strategy of Learning Tournament type. The purpose of this rese was by implementing active learning strategy of Learning Tournament type. The purpose of this research was answering the research question whether implementing active learning strategy of Learning Tournament type gave better improvement in studentsâ learning motivation and studentsâ comprehension of mathematical concept than by using conventional learning strategy. This strategy applied to student Grade VIII SMPN 5 Koto XI Tarusan. The type of this research was experimental research. The population in this research was the students grade VIII SMPN 5 Koto XI Tarusan year 2013/2014. The technique in choosing research sample was random sampling technique, which chose class VIII.3 as an experimental class VIII.1 as a control class. The instrument in this research was questionnaire and final tes. Questioner was used to see the differentiation of motivation score in the questioner which given in the beginning of the research and in questioner which given in the end of the research. Then, researcher also used final test by using comprehension of the concept as the indicator. The technique of data analysis was t test which was analyzed by using MINITAB. Based on the data analysis, it was known that two sample had normal disrtributions and homogenizes and hypothesis test shown P-value was last them <ð¼. So, hypothesis could be accepted. In conclusion, comprehension of mathematic concept of students Grade VIII SMPN 5 Koto XI Tarusan which was taught by using active learning strategy og Learning Tournament type got better improvement than their comprehension of mathematical concept by using conventional.